2012
DOI: 10.1016/j.molcel.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate Kinase M2 Regulates Gene Transcription by Acting as a Protein Kinase

Abstract: Summary Pyruvate kinase isoform M2 (PKM2) is a glycolysis enzyme catalyzing conversion of phosphoenolpyruvate (PEP) to pyruvate with transferring a phosphate from PEP to ADP. We report here that PKM2 localizes to the cell nucleus. The levels of nuclear PKM2 correlate with cell proliferation. PKM2 activates transcription of MEK5 by phosphorylating stat3 at Y705. In vitro phosphorylation assays show that PKM2 is a protein kinase using PEP as phosphate donor. ADP competes with the protein substrate binding, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
688
2
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 647 publications
(709 citation statements)
references
References 38 publications
11
688
2
8
Order By: Relevance
“…Additionally, size-exclusion chromatographic analysis of various combinations of purified recombinant proteins [PKM2/ R399E, a dimeric mutant (15); and/or JMJD5/ JMJD5ΔN80 (a binding-defective mutant)] clearly demonstrates that the tetrameric formation of PKM2 is hindered by JMJD5 but not JMJD5ΔN80, confirming that JMJD5 influences the PKM2 oligomerization via a direct binding (Fig. S6).…”
Section: Jmjd5 Knockdown Reduces Cell Growth and Glycolytic Genes In mentioning
confidence: 81%
See 3 more Smart Citations
“…Additionally, size-exclusion chromatographic analysis of various combinations of purified recombinant proteins [PKM2/ R399E, a dimeric mutant (15); and/or JMJD5/ JMJD5ΔN80 (a binding-defective mutant)] clearly demonstrates that the tetrameric formation of PKM2 is hindered by JMJD5 but not JMJD5ΔN80, confirming that JMJD5 influences the PKM2 oligomerization via a direct binding (Fig. S6).…”
Section: Jmjd5 Knockdown Reduces Cell Growth and Glycolytic Genes In mentioning
confidence: 81%
“…19). Gao et al recently showed that the nuclear PKM2 was mainly present as a dimer (15). Notably, Yang et al (18) found that PKM2 was phosphorylated at the segment involved in multimeric assembly by Erk2, implicating that the monomeric form is crucial for the phosphorylation of PKM2 and its nuclear translocation.…”
Section: Jmjd5 Knockdown Reduces Cell Growth and Glycolytic Genes In mentioning
confidence: 99%
See 2 more Smart Citations
“…This reason may be that different dosages and treating time of have different effects on the proliferation of some cell lines, PKM2 is a key glycolytic enzyme that regulates the Warburg effect and is necessary for tumor growth (Wong et al, 2013). Recent studies indicated that nuclear PKM2 could activate gene transcription and cell proliferation in human glioblastoma, prostate cancer and breast cancer cells (Gao et al, 2012;Lee et al, 2008;Luo et al, 2011a;Luo et al, 2011b). Here we observed its role in EGFinduced EMT and cell motility in HCC cells.…”
Section: Discussionmentioning
confidence: 99%